Developing mobile E-groceries model - Othman, Muhammad Fauzi; Amir, Nursihah; Mansu, Muhifuudin; Zeki, Akram M. (The Institute of Electrical and Electronics Engineers, Inc., 2016)
In a traditional groceries market, various business models have been implemented. Most of these models failed due to e-grocery retailing process. This has led to many inefficient operation of the groceries market in many parts of the world. Previous studies have shown the application and success of e-Groceries system in a web based scheme. This paper tries to develop a prototype for e-Groceries system on android platform suitable for most mobile devices. The system's objective includes introducing a new way of grocery shopping especially for Malaysians. The development of the system follows the generic software development process. Thus we provide a detailed system development and its implementation. During implementation we call the system as MyMart e-Groceries system. Users can select various types of groceries in a simple and friendly mobile user interface and pay for the selected choice, which will be subsequently delivered to their door steps.